Influence of weed management practices and dates of transplanting in tomato (Solanum lycopersicum) - TOMAR, SAURABH; RAJIV,; SINGH, D P; SRIVASTAVA, A K; JAWLA, SUBHASH KUMAR; KUMARI, MEENAKSHI; MALIK, ANURAG; DEV, PAVITRA (The Indian Journal of Agricultural Sciences, 2021)
The field experiment was conducted during two consecutive years 2016-17 and 2017-18 to find out the influence of weed management practices and dates of transplanting on weed, fruit yield and profitability of tomato (Solanum lycopersicum L.) at Vegetable Research Farm of Chandra Shekhar Azad University of Agricultural and Technology, Kanpur. The experiment was laid out in factorial randomized block design (FRBD) with four different dates of transplanting, viz. 15 October, 31 October, 15 November and 30 November and four type of mulches, viz. black polyethylene, white polyethylene, bio-mulch (paddy straw) and control (without mulch) replicated thrice. Tomato cultivar Azad T-6 was used in experiment. Results of the experiment revealed that the minimum weed population (4.43 and 4.26/m2) and weeds fresh weight (9.52 and 9.15 g/m2) and significantly highest marketable yield (30610 and 31418 kg/ha) and net returns (` 241460.50 and 249538.00/ha) were recorded in crop transplanted on 30 October. In case of mulching, application of bio-mulch (paddy straw) recorded minimum weed population (4.88 and 4.76/m2) and weeds fresh weight (10.48 and 10.28 g/m2) and significantly highest marketable yield (29569 and 30354 kg/ha) and net returns (` 231050.50 and 238905.50/ha). Transplanting on 30 October and application of bio-mulch (paddy straw) proved to be the best treatment combination for effective weed management and enhancing productivity and profitability of tomato. Therefore, this practice may be recommended to exploit the better economic yield of tomato under central plain zone of Uttar Pradesh.